Implementation of Organizational Culture and Personal ISO at PT. Anindya Wiraputra Konsult Kendari Branch - Lilik Rita Lindayani; Awaluddin Muh. Nur; Nurmin Suryati; La Sudu; Irma Magara; Lestrariwati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This article discusses the Team FIB-UHO industrial visit, as well as efforts to strengthen organizational culture in implementing the ISO Quality Management System at PT. Anindya Wiraputra Konsult (ANINDYA) Kendari Branch. This activity aims to open up space for collaboration regarding industrial literacy and the world of work for campuses by looking at the implementation of the ISO system in supporting partner activities and paying attention to factors that support and hinder its implementation. The ISO Quality Management System, starting from ISO 9001, ISO 14001, ISO 45001, to ISO 17020 certification, has an impact on activities at ANIDYA and the expansion of the world of work. The activity technique is carried out using collaborative observation, in-depth observation results, document analysis, and questions and answers with staff and partner employees selected purposively, as well as distributing questionnaires to clients. Data shows that the quality of human resources in the industrial world is not just a diploma, but also requires personal certification, as well as consistent and continuous training. Other results show strict and evaluative process standards, as well as a positive attitude and culture as a professional company that places competitors as benchmarks to support strengthening the quality and quantity of work, strategically providing service satisfaction to consumers and profit value for the company.